KINERJA PELAYANAN PENDIDIKAN BAGI ANAK BERKEBUTUHAN KHUSUS PADA SEKOLAH LUAR BIASA NEGERI 1 AMUNTAI KECAMATAN AMUNTAI TENGAH KABUPATEN HULU SUNGAI UTARA - Anjasmari, Ni Made Musiyani (Administraus, 2022)
Special School (SLB) is a school for children with special needs (ABK). The purpose of providing education for children with special needs is to be independent and empowered so that they can carry out their lives in the future. However, there are problems that arise related to the performance of educational services for ABK at SLB Negeri 1 Amuntai, namely there are still graduate educators outside special education, classrooms are not differentiated by type of disability, less varied learning process, and lack of facilities and school infrastructure. This research was taken to determine the performance of educational services for children with special needs and the factors that influence it and the efforts that have been made. The study used a qualitative descriptive method with data collection through observation, interviews and documentation. The data source was taken through purposive sampling with a total of 12 people. After the data has been collected, it is analyzed using techniques including data reduction, data presentation, verification / conclusion, and data credibility testing. The results of the study indicate that the performance of education services for children with special needs at SLB Negeri 1 Amuntai, Amuntai Tengah District, Hulu Sungai Utara Regency is still not good. First, the productivity aspect of efficiency, input and output has not been good. Second, the aspect of service quality in the learning strategy, learning media and the availability of learning tools is still not good. Third, the responsiveness aspect of the ability of teaching staff and following up on problems is good, but the ability to carry out assessments is not good. Fourth, the aspect of responsibility in accordance with the principle is good. Fifth, the accountability aspect of the responsibility indicator is good. The factors that affect: First, the lack of teaching and education personnel, the ratio of the number of teachers and subjects is not comparable, not all teachers have skills, lack of infrastructure and cooperation with parents of students, school environment. Second, the supporting factors, namely: modification of the appropriate curriculum, teamwork and working with a patient and respectful attitude. Efforts made to overcome the inhibiting factor are that the teaching staff has attended training to improve their abilities and strive to fulfill the facilities and infrastructure. To improve the performance of education services for ABK at SLB Negeri 1 Amuntai, it is advisable for the Principal to add educators and education personnel. Then for the teaching staff, they should improve their performance more creatively. Parents of students should always accompany their children at home. And the community is expected to be able to actively care and be able to provide opportunities to work and work like others.